The Expositor's Bible Commentary, with The New International Version of The Holy Bible: Volume 11: Ephesians- Philemon - Frank Ely Gaebelein 1899-1983; James Dixon Douglas; Dick Polcyn (USA Zondervan Publishing House, 1984)
The seventy-eight contributors to the Expositor's Bible Commentary come from the United States, Canada, England, Scotland, Australia, and New Zealand, and from many denominations, including Anglican, Baptist, Brethren, Methodist, Nazarene, Presbyterian, and Reformed. The Expositor's Bible Commentary uses the New International Version for its English text, but also refers freely to other translations and to the original languages. Each book of the Bible has, in addition to its exposition, an introduction, outline, and bibliography. Notes on textual questions and special problems are correlated with the expository units; transliteration and translation of Semitic and Greek words make the more technical notes accessible to readers unacquainted with the biblical languages. In matters where marked differences of opinion exist, commentators, while stating their own convictions, deal fairly and irenically with opposing views. --From publisher's description.
general editor, Frank E. Gaebelein ; associate editor, J.D. Douglas ; consulting editors ... Walter C. Kaiser, Jr. [and others].
Associate editor, 1985-1992: Richard P. Polcyn. . Ephesians / A. Skevington Wood. Philippians / Homer A. Kent Jr. Colossians / Curtis Vaughan. 1, 2 Thessalonians / Robert L. Thomas. 1, 2 Timothy / Ralph Earle. Titus / D. Edmond Heibert. Philemon / Arthur A. Rupprecht.
Vols. 2, 4, 6-8 published by Regency Reference Library.
Keywords: Holy Bible Commentary Series (3SdGSd JaSjQ GdcJGH GdebOSs; Bible